Toward Bio-based geo- & Civil Engineering for a Sustainable Society. (2017) - Jonkers, Henk M.
Abstract: The since 2010 running research program 'Bio-Based Geo & Civil Engineering for a Sustainable Society (BioGeoCivil)', funded by the Dutch technology foundation STW, aims to develop novel bio-based construction materials that can be used in Civil- and Geo-engineering constructions to enhance the sustainability performance of the sector. Rationale is that the sector produces still today excess amounts of waste in all life cycle phases of a construction, from building to use phase as well as end-of-life phase. Aim of the program is to mimic nature as 'building' processes in nature do not produce any waste as all elements, also residual material. is considered a high grade resource. In order to substantially improve the sustainability profile of the sector, upgrading of secondary- or byproducts must be achieved to allow functional performance similar to primary materials and resources. The challenge of the six currently running projects within the BioGeoCivil program is therefore not only to mimic nature but also to include bio-based materials or processes in civil- or geo-engineering applications which result, in comparison to traditional building products, in drastically improved performance both on sustainability and durability level. The six projects comprise: 1. Fungal biofilms (coating) for wood protection, 2. Bacteria-based repair and performance improvements of aged concrete structures, 3. Bacteria-based ground stabilization to mitigate liquefaction and piping of granular sediments, 4. Engineering of bacterial biofilms on buildings and infrastructure as a basis for natural protection, 5. Lift up Lowlands: upgrading of natural materials (bio-remediation of sludge) for sustainable lift up of low lying polder areas, and 6. Towards the development of carbon dioxide neutral renewable cement.